Supervision of Apprentices in Semiskilled Trades: Program Stipulations and Workplace Realities - Laberge, Marie; Vézina, Nicole; Calvet, Bénédicte; Lévesque, Sophie; Vézina-Nadon, Livann (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
An ergonomics intervention research study was carried out with an aim to prevent workplace injury for students enrolled in the Training for a Semiskilled Trade (TST) vocational program, which was recently instituted in Quebec, Canada. The article lays out certain discrepancies between the institution-prescribed parameters for TST intern supervision and workplace realities, in order to best determine the foundations upon which workplace injury prevention programs might be based. With this goal in mind, the article outlines some aspects of the social setting encountered upon entering the workforce, specifically communications with colleagues and access to guidance and support in the workplace. Methods were based on analysis of ministerial and institutional training documentation and a two-wave data collection protocol comprising individual interviews with interns and observation of work situations to document the orientation and training process. Results showed that workplace supervisory conditions are rather different from what is described in the training program documentation. Several students, contrary to program specifications, find themselves in incidental work situations involving supervising colleagues who have unofficially elected or accidentally taken on such roles. Access to supervision and guidance is not always promptly provided, meaning young workers are left without structured help and support. Furthermore, apprentices find themselves in an incredibly diverse range of contexts and settings. Hence, it should be deemed essential to develop flexible teaching and learning tools which can apply or be adapted to a variety of contexts. The training program’s traditional supervisor-apprentice partnership model would be best revised to maximize the use of all valuable on-site resources and ensure students develop skills to stay healthy at work.